A Genetic Linkage Map Of Asian Seabass, Lates Calcarifer Using Dna Microsatellite Markers In Application To Quantitative Trait Loci (Qtl) - Razak, Mohd Shahril Firdaus Ab (2012)
Genetic linkage maps of Asian sea bass have been established using a mapping panel containing a pair of parent (1 male and 1 female) and their 160 progenies. This mapping panel was obtained from parentage assignment from mass breeding programme using DNA microsatellite markers. In parentage assignment, a total 24 pairs of microsatellite markers have been used to screen all broodstock. The analyses result showed the number of alleles per locus ranged from 3 to 14 with an average of 6.65 alleles per locus and the values of the observed and expected heterozygosities ranged from 0.121 to 1.000 and from 0.198 to 0.857 respectively. The average of PIC was 0.515 with range from 0.186 to 0.826. From this analysis, only five microsatellite markers were used in parentage assignment since these 5 markers show high polymorphism level. In parentage analyses, 94.9% were successfully assigned to a single or double parent pair and only 51 (5.1%) individual progenies were left unassigned since these individual were genotyped for fewer than 2 loci. A single parent pair with their progeny have been selected and used as a mapping panel in linkage mapping construction. In linkage analyses, a total of 273 microsatellite markers have been used. Out of 273 markers, only 210 microsatellite markers (76.9%) were successfully mapped into 24 linkage groups (labelled LG1- LG24) at minimum 3.0 LOD value and maximum distance at 50.0 cM (centiMorgan).